In Vitro and In Vivo Effects of the Bumped Kinase Inhibitor 1294 in the Related Cyst-Forming Apicomplexans Toxoplasma gondii and Neospora caninum - Winzer, Pablo (Antimicrob Agents Chemother, 2015)
We report on the in vitro effects of the bumped kinase inhibitor 1294 (BKI-1294) in cultures of virulent Neospora caninum isolates Nc-Liverpool (Nc-Liv) and Nc-Spain7 and in two strains of Toxoplasma gondii (RH and ME49), all grown in human foreskin fibroblasts. In these parasites, BKI-1294 acted with 50% inhibitory concentrations (IC(50)s) ranging from 20 nM (T. gondii RH) to 360 nM (N. caninum Nc-Liv), and exposure of intracellular stages to 1294 led to the nondisjunction of newly formed tachyzoites, resulting in the formation of multinucleated complexes similar to complexes previously observed in BKI-1294-treated N. caninum beta-galactosidase-expressing parasites. However, such complexes were not seen in a transgenic T. gondii strain that expressed CDPK1 harboring a mutation (G to M) in the gatekeeper residue. In T. gondii ME49 and N. caninum Nc-Liv, exposure of cultures to BKI-1294 resulted in the elevated expression of mRNA coding for the bradyzoite marker BAG1. Unlike in bradyzoites, SAG1 expression was not repressed. Immunofluorescence also showed that these multinucleated complexes expressed SAG1 and BAG1 and the monoclonal antibody CC2, which binds to a yet unidentified bradyzoite antigen, also exhibited increased labeling. In a pregnant mouse model, BKI-1294 efficiently inhibited vertical transmission in BALB/c mice experimentally infected with one of the two virulent isolates Nc-Liv or Nc-Spain7, demonstrating proof of concept that this compound protected offspring from vertical transmission and disease. The observed deregulated antigen expression effect may enhance the immune response during BKI-1294 therapy and will be the subject of future studies.